Reconstruction of a Digital Economy Model Based on Islamic Justice Values in Addressing Global Financial Technology Disruption - Dewi Suryaningsih Saputri; Ernawati; Nugroho Noto Diharjo (Khazanah: Journal of Islamic Education and Science, 2025)
Global financial technology disruption has restructured the architecture of the digital economy through platformization, algorithmic governance, and financial decentralization, thereby reshaping value distribution and the concentration of economic power. These transformations have generated critical challenges to distributive justice from the perspective of Islamic economics. This study aimed to reconstruct a digital economic model grounded in Islamic justice values in response to global financial technology disruption. The research employed a qualitative descriptive approach using a systematic literature review of scholarly publications from 2017 to 2024 indexed in national and international academic databases. Data were analyzed through content and thematic analysis to synthesize conceptual and empirical findings. The results indicated that most existing Islamic digital economic models remained adaptive to the architecture of digital capitalism and had not systematically integrated maqasid al-shariah principles into governance design and value distribution mechanisms. This study proposed a reconstruction model based on ontological, epistemological, institutional, and regulatory dimensions that positioned justice as the foundational architecture of the digital economy. The study contributed an integrative conceptual framework that advanced contemporary Islamic economic discourse within the context of global digital transformation.